PENGENALAN VMWARE INFRASTRUCTURE AS A SERVICE SEBAGAI METODE KOMPUTASI VIRTUAL GUNA MENGOPTIMALISASI PENGGUNAAN DAN KINERJA PERANGKAT KERAS DI SMA AL MUHTADIN DEPOK - Aditia; Muhamad Hanafi; Bagus Muhammad Saputra; Muhammad Rio Arya Pratama; Miftah Aziz; Sifa fauziah; Ade Rosadi (Abdi Jurnal Publikasi, 2022)
Every higher education institution in the territory of Indonesia is required to carry out these Tridharma. The term community service in Law no. 12 of 2012 paragraph 10 is defined as the activities of academics who utilize Science and Technology to promote community welfare and educate the nation's life. The academic community in question is the academic community consisting of lecturers and students. Pamulang University, especially the Informatics Engineering study program, always provides support and trust to academics to be able to carry out the Tri Dharma of Higher Education, one of which is community service. This Community Service activity for the Odd Semester 2022/2023 is being carried out at Al Muhtadin Vocational School. The material provided is in the form of Virtualization training using VMware licensed software, while the details of the activities include introduction and training related to network and virtualization concepts.